PENGARUH KOMBINASI SUSU KACANG KEDELAI DAN PENGENCER SITRAT KUNING TELUR TERHADAP KUALITAS SEMEN SAPI BALI (Effect of combination soy bean milk and citrate egg yolk liqid on the quality of bali cattle semen) - Maria E.E. Fernandez; Wilmientje M Nalley; Franky M.S. Telupere; Thomas M. Hine (Universitas Nusa Cendana, 2022)
One of the diluent containing lipoproteins and lecithins that function in maintaining and protecting the integrity of the plasma membrane of spermatozoa from cold shock is soy milk. The purpose of this study was to determine the effect of the combination of soy bean milk and egg yolk citrate liqud on the quality of liquid semen of bali cattle. The material used in this study was fresh semen of 3 year old bali cattle. Semen was diluted with egg yolk citrate diluent with a combination of soy bean milk, namely T0: 100% citrate egg yolk (CEY); T1: CEY 75%+soy bean milk (SBM) 25%; T2: CEY 50%+SBM 50%; T3: CEY 25%+SBM 75%; and T4: 100% SBM. Liqud semen was stored at a temperature of 3-5oC. The parameter studied were motility, viability, abnormality and liveability of spermatozoa. The research data ware analyzed using an analysis of variance (ANOVA) and followed by the multiple range test. The results showed that T1 significantly difference (P<0.05) from other treatments, with motility of 42.40±2.50%, viability 52.15±6.31%, abnormality 6.44±0.84%, and liveability 6.00±0.00 days. From these result it could be concluded that the combination of 25% soy bean milk and 75% egg yolk citrate liqud was the best treatment, and spermatozoa can be stored until six days.